130 Does visual imagery vividness have a genetic basis? A genome-wide associa- tion study of 1019 individuals. Issue 6 (27th May 2022) - Day, Jacob; Frayling, Timothy; Wood, Andrew; Zeman, Adam
Abstract : The vividness of visual imagery varies widely between individuals and its extremes are associated with prosopagnosia and synaesthesia. A complete lack of visual imagery, recently termed aphantasia, is typically present from birth and is more common in those with affected family members. It is therefore postulated that there is a genetic component to the variation in visual imagery vividness. To try and identify genetic variants associated with visual imagery vividness we performed a genome-wide association study of 1019 individuals in the Exeter 10000 cohort. Participants who had previously been genotyped were then asked to complete the Vividness of Visual Imagery Questionnaire (VVIQ). We did not identify any variants that reached the genome-wide significance p<5x10–8 level. However, 2 variants in linkage disequilibrium were below the p<5x10–7 level and lie within an intron of the SYT1 gene which encodes a protein important in neuronal synaptic transmission. There were no significant genetic correlations with VVIQ and other publicly available traits. Further work should focus on using larger cohorts which will have greater power to identify variants which account for smaller amounts of VIVQ variance. This would also determine whether the SYT1 variant is truly significant. jacobday@doctors.org.uk